Diversity of Insect Pests on Two Varieties of Bird’s Eye Chilli (Capsicum frutescens L.) Under the Intercropping System in Sidamukti Village, Baros District, Serang Regency - Rizqita Amalia Putri; Rusmana Rusmana; Widia Eka Putri; Andree Saylendra (Jurnal Agroekoteknologi Terapan, 2025)
The diversity of insect pests plays an important role in determining crop yield and quality. This study aims to examine the diversity, evenness, dominance, and types of insect pests found on two varieties (Ori 212 and Or Trisula Hijau) of bird’s eye chilli (Capsicum frutescens L.) under an intercropping system in Sidamukti Village, Baros District, Serang Regency, Banten. The purposive sampling method used was purposive sampling. Sample points were systematically determined along a diagonal line. Thus, in each plot of the bird’s eye chilli varieties, there were five sampling points. Insects were collected using sweep nets and yellow pan traps, preserved in 70% alcohol, then identified and counted. The results of the study revealed five genera of insect pests: Bactrocera sp., Gryllus sp., Oxya sp., Nilaparvata sp., and Aphis sp. The diversity index was moderate, the evenness index was relatively high, and the dominance index was relatively low in the two bird’s eye chilli varieties studied. Keywords: Bird’s Eye Chilli, Pest, Diversity, Insects